Խնուսի խոսվածքի դրսևորումները Ռուսաստանի դաշնությունում - Արոսյան Մարիա (ԳԱԱ ԼԻ հրատ․)
Структурный и статистический анализ данных опроса, видов связей и степени близости показал нам, что сохранение, развитие и распространение диалекта очень важно для сохранения и развития армянского языка и армянских ценностей. Как говорилось выше, анализ установил прочную прямую связь между знанием современного армянского языка и использованием диалекта.Для наших соотечественников, проживающих в чужой стране, диалект может стать серьезным барьером во избежание риска ассимиляции. А также более глубокое изучение стремления носителей диалекта общаться только или преимущественно на своем диалекте может стать основой для укрепления современного армянского языка, чтобы язык стал более конкурентоспособным и считался основным языком общения. The structural and statistical analysis of the survey data, the types of connections and the degrees of closeness showed us that the preservation, development and dissemination of the dialect is very important for the preservation and development of the Armenian language and Armenian values. As mentioned above, during the analysis, there was a close direct connection between the knowledge of modern Armenian and the use of the dialect. For our compatriots living in a foreign country dialect can be a serious barrier to avoid the risk of assimilation.as well as the deeper study of dialect speakers' desire to communicate only or mainly in their own dialect can be the basis for making the modern Armenian language even stronger and more competitive, so that it is considered the main language of communication for families in a foreign country.
Keywords: Հայոց լեզու; Լեզվաբանություն